CD8 + T cell immunity Is compromised by Anti-CD20 treatment and rescued by Interleukin-17A - Fiocca Vernengo, Facundo (2020)
Treatment with anti-CD20, used in many diseases in which B cells play a pathogenic role, has been associated with susceptibility to intracellular infections. Here, we studied the effect of anti-CD20 injection on CD8+ T cell immunity using an experimental model of Trypanosoma cruzi infection, in which CD8+ T cells play a pivotal role. C57BL/6 mice were treated with anti-CD20 for B cell depletion prior to T. cruzi infection. Infected anti-CD20-treated mice exhibited a CD8+ T cell response with a conserved expansion phase followed by an early contraction, resulting in a strong reduction in total and parasite-specific CD8+ T cell numbers at 20 days postinfection. Anti-CD20 injection increased the frequency of apoptotic CD8+ T cells, decreased the number of effector and memory CD8+ T cells, and reduced the frequency of proliferating and cytokine-producing CD8+ T cells. Accordingly, infected anti-CD20-treated mice presented lower cytotoxicity of T. cruzi peptide-pulsed target cells in vivo. All of these alterations in CD8+ T cell immunity were associated with increased tissue parasitism. Anti-CD20 injection also dampened the CD8+ T cell response, when this had already been generated, indicating that B cells were involved in the maintenance rather than the induction of CD8+ T cell immunity. Anti-CD20 injection also resulted in a marked reduction in the frequency of interleukin-6 (IL-6)- and IL-17A-producing cells, and recombinant IL-17A (rIL-17A) injection partially restored the CD8+ T cell response in infected anti-CD20-treated mice. Thus, anti-CD20 reduced CD8+ T cell immunity, and IL-17A is a candidate for rescuing deficient responses either directly or indirectly.